Estimation of the burden of cardiovascular disease attributable to modifiable risk factors and cost-effectiveness analysis of preventative interventions to reduce this burden in Argentina - Martí Sebastián; Caporale Joaquín; Bardach Ariel; Colantonio Lisandro; Rubinstein Adolfo; Kopitowski Karin; Alcaraz Andrea; Gibbons Luz; Augustovski Federico; Pichón-Rivière Andrés (BMC, 2010)
Abstract Background Cardiovascular disease (CVD) is the primary cause of mortality and morbidity in Argentina representing 34.2% of deaths and 12.6% of potential years of life lost (PYLL). The aim of the study was to estimate the burden of acute coronary heart disease (CHD) and stroke and the cost-effectiveness of preventative population-based and clinical interventions. Methods An epidemiological model was built incorporating prevalence and distribution of high blood pressure, high cholesterol, hyperglycemia, overweight and obesity, smoking, and physical inactivity, obtained from the Argentine Survey of Risk Factors dataset. Population Attributable Fraction (PAF) of each risk factor was estimated using relative risks from international sources. Total fatal and non-fatal events, PYLL and Disability Adjusted Life Years (DALY) were estimated. Costs of event were calculated from local utilization databases and expressed in international dollars (I$). Incremental cost-effectiveness ratios (ICER) were estimated for six interventions: reducing salt in bread, mass media campaign to promote tobacco cessation, pharmacological therapy of high blood pressure, pharmacological therapy of high cholesterol, tobacco cessation therapy with bupropion, and a multidrug strategy for people with an estimated absolute risk > 20% in 10 years. Results An estimated total of 611,635 DALY was lost due to acute CHD and stroke for 2005. Modifiable risk factors explained 71.1% of DALY and more than 80% of events. Two interventions were cost-saving: lowering salt intake in the population through reducing salt in bread and multidrug therapy targeted to persons with an absolute risk above 20% in 10 years; three interventions had very acceptable ICERs: drug therapy for high blood pressure in hypertensive patients not yet undergoing treatment (I$ 2,908 per DALY saved), mass media campaign to promote tobacco cessation amongst smokers (I$ 3,186 per DALY saved), and lowering cholesterol with statin drug therapy (I$ 14,432 per DALY saved); and one intervention was not found to be cost-effective: tobacco cessation with bupropion (I$ 59,433 per DALY saved) Conclusions Most of the interventions selected were cost-saving or very cost-effective. This study aims to inform policy makers on resource-allocation decisions to reduce the burden of CVD in Argentina.